The paradoxes of inclusion: cognitive and socio-emotional developmental trajectories of deaf and blind primary education students in mainstream and special schools - Rosas, Ricardo; Espinoza, Victoria; Martinez, Camila; Santa-Cruz, Catalina (Frontiers in Education, 2023)
Introduction Students with special educational needs (SEN) have historically found participating in the regular education system challenging. Since the 1990s, inclusion has been considered the optimal strategy for their development. However, the effects of inclusive education on deaf and blind students are still little studied. Methods In the present article, we report the results of a longitudinal study on the cognitive and socioemotional developmental trajectories of 23 deaf and 29 blind primary education students attending mainstream (8 deaf and 10 blind) and special schools (15 deaf and 19 blind). The study was conducted in Santiago de Chile between 2018 and 2019. Results Our descriptive results suggest that deaf students attending special schools perform better on most of the variables studied. For blind students, those attending traditional schools generally perform better than those attending special schools. However, in the case of socio-emotional variables, blind students attending special schools tend to show fewer problems. However, almost all of the indicated differences are not statistically significantly different. Discussion We then discuss the need to consider the characteristics of each group of students with SEN when defining an adequate educational system for their optimal development.